2016
DOI: 10.1016/j.ebiom.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacogenomics Finds RUNX1 Is an Aspirin-Responsive Transcription Factor Linked to Cardiovascular Disease and Colon Cancer

Abstract: Aspirin prevents cardiovascular disease and colon cancer; however aspirin's inhibition of platelet COX-1 only partially explains its diverse effects. We previously identified an aspirin response signature (ARS) in blood consisting of 62 co-expressed transcripts that correlated with aspirin's effects on platelets and myocardial infarction (MI). Here we report that 60% of ARS transcripts are regulated by RUNX1 – a hematopoietic transcription factor - and 48% of ARS gene promoters contain a RUNX1 binding site. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Thus, higher PCTP expression is associated with a higher risk of cardiovascular events. In a separate CATHGEN analysis, 16 we previously showed that RUNX1 P1 probe sets (233690_at and 220918_at) are significantly lower in CATHGEN patients who develop death or MI. Of the RUNX1 P2 probe sets described above, one 211181_x_at was associated with higher risk of death/MI in CATHGEN (OR = 3.3 [1.5–7.3], p-value = 0.003.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Thus, higher PCTP expression is associated with a higher risk of cardiovascular events. In a separate CATHGEN analysis, 16 we previously showed that RUNX1 P1 probe sets (233690_at and 220918_at) are significantly lower in CATHGEN patients who develop death or MI. Of the RUNX1 P2 probe sets described above, one 211181_x_at was associated with higher risk of death/MI in CATHGEN (OR = 3.3 [1.5–7.3], p-value = 0.003.…”
Section: Resultsmentioning
confidence: 87%
“…Several potential probe sets available on the Affymetrix microarray map to the RUNX1 locus on chromosome 21. Of the 17 available probe sets, we selected 6 that map to a single locus in the genome and had evidence by PCR for being able to discriminate between RUNX1 P1 vs. P2 expression by PCR (Supplemental Table 5) as previously described 16,27 . To select microarray probe sets for RUNX1 we used banked, serial peripheral blood RNA from healthy volunteers with matched microarray data 27 and performed PCR for RUNX1 isoforms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] Growing evidence has revealed that miRNAs play an important role in carcinogenesis and cancer progression. Depending on their mRNA targets, miRNAs can act as oncogenes or tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%